2004
DOI: 10.1073/pnas.0305555101
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of the homeobox gene Cdx2 is the transforming event in a mouse model of t(12;13)(p13;q12) acute myeloid leukemia

Abstract: Creation of fusion genes by balanced chromosomal translocations is one of the hallmarks of acute myeloid leukemia (AML) and is considered one of the key leukemogenic events in this disease. In t(12;13)(p13;q12) AML, ectopic expression of the homeobox gene CDX2 was detected in addition to expression of the ETV6-CDX2 fusion gene, generated by the chromosomal translocation. Here we show in a murine model of t(12;13)(p13;q12) AML that myeloid leukemogenesis is induced by the ectopic expression of CDX2 and not by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 43 publications
3
103
1
Order By: Relevance
“…The authors concluded that activation of proto-oncogenes might be a more common phenomenon in ETV6 associated leukaemia than was previously thought. 30,53 Our case was different in that the promoter in intron 2 was deleted, suggesting that the promoter upstream of exon 1 was the one involved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that activation of proto-oncogenes might be a more common phenomenon in ETV6 associated leukaemia than was previously thought. 30,53 Our case was different in that the promoter in intron 2 was deleted, suggesting that the promoter upstream of exon 1 was the one involved.…”
Section: Discussionmentioning
confidence: 99%
“…30 The ectopic expression of intact CDX2 rather than the ETV6-CDX2 fusion proved essential for leukaemogenesis. 53 Reports of lymphoid malignancies include a B-cell precursor cell line in which the STL gene at 6q23 was the partner 26 and a case of paediatric pre-B ALL, the BAZ2 gene at 12q13. 29 Our three cases thus add significantly to the lymphoid examples.…”
Section: Discussionmentioning
confidence: 99%
“…Whole BM NA Aggressive AML (100%) Splenomegaly, anaemia undifferentiated myeloblasts in BM, S + PB (Rawat et al, 2004) Abbreviations: ALL, acute lymphocytic leukaemia; AML, acute myeloid leukaemia; APL, acute promyelocytic leukaemia ATRA, all-trans retinoic acid; BM, bone marrow; MPD, myeloproliferative disease; NA, not available; NOD/SCID, non-obese diabetic/severe combined immunodeficiency disease; PB, Peripheral blood; S, spleen; WBC, white blood cell count.…”
Section: Cdx2mentioning
confidence: 99%
“…7 For transduction of Cdx2, cells were co-cultured with irradiated (4000 cGy from a 137 Cs g-radiation) GP þ E86 Cdx2 producer cells. Clonogenicity of short hairpin RNA (shRNA) transduced Nalm6 cells was analyzed in the CFC assay as described earlier (Methocult H4434, Stemcell Technologies, Vancouver, British Colombia, Canada).…”
Section: Retroviral Infection and In Vitro Assaysmentioning
confidence: 99%
“…[3][4][5] However, for the majority of ALL cases the molecular mechanisms driving the malignant transformation are unknown. Recently, data from experimental models and gene expression profiling in patients with acute myeloid leukemia (AML) have identified CDX2 as a powerful oncogene when aberrantly expressed in adult hematopoietic progenitor cells: [6][7][8] the 'caudal related homeobox gene' CDX2 belongs to the family of so-called 'ParaHox genes', which also includes CDX1, CDX4 and the GSH2 homeobox gene. 9 Normally expression of CDX2 is tightly regulated in the adult organism, with expression in the intestine but no expression in adult hematopoietic tissue.…”
Section: Introductionmentioning
confidence: 99%